Music and mass communication: a study of M. Nasir and modern Malay music / Amir Husairi Sharif - Sharif, Amir Husairi (2006)
This study focuses on the evolution of modern Malay music in Malaysia with reference to the person of M. Nasir. Such a study is relatively new in the Malaysian context. This study sees that the time has come to seriously investigate the various dimensions and implications of this aspect of popular culture through a socio-historical and a biographical approach. Hence, the study was divided into two parts: the first part surveys the development and evolution of music from a socio-historical perspective; while the second part examines the roles of M. Nasir in influencing the path of Malay popular music. It also made reference to ideas that have influenced M. Nasir and which in turn was seen to be reflected in his music. This study can be seen as an attempt to sketch a biography of the person as composer, singer and artist. From such an investigation, we can conclude that there is much more than what seems to be merely entertainment. Modern Malay popular music, like the Rock genres of the 1960s and '70s, reflect the mood of political and social life of the times. To some extent, it embodies a certain outlook in social criticism, a search for meaning, and a form of political protest.